IMPACT OF SOFT GELATIN CAPSULES FORMULATIONS FOR ORAL ADMINISTRATION - BODAVULA.SAMBA SIVA RAO (International Journal of Pharma and Bio Sciences, 2014)
Soft gelatin capsules are also known as soluble elastic or soft elastic capsule.The composition of soft gelatin capsule differs from hard gelatin capsule in that sugar the sugar is replaced by a plasticizer like glycerin ,sorbitol or a similar polyol.plasticizer impart elastic properties to capsules.The soft gelatin capsules are hermetically sealed they are suitable for liquids,volatile drugs and for drugs sensitive to atmospheric oxidation. This has led to the commercial pharmaceutical and nutraceutical industries opting for the development of alternative shell forming materials instead of the traditional capsule shell material gelatin. This review discusses the establishment and the on-going development of the manufacturing technology for liquid fill capsules with a focus on the progress and challenges of soft gelatin capsules formulation in oral administration for improved solubility and as an absorption-enhancing technique. This considerations form a basis for new applications in oral drug.